Identification of a Sphingolipid α-Glucuronosyltransferase That Is Essential for Pollen Function in Arabidopsis . Issue 8 (8th August 2014) - Rennie, Emilie A.; Ebert, Berit; Miles, Godfrey P.; Cahoon, Rebecca E.; Christiansen, Katy M.; Stonebloom, Solomon; Khatab, Hoda; Twell, David; Petzold, Christopher J.; Adams, Paul D.; Dupree, Paul; Heazlewood, Joshua L.; et al.
Abstract : This study found that IPUT1 is an enzyme required for the biosynthesis of glycosyl inositol phosphorylceramide sphingolipids in plants. These glycolipids are highly abundant and have many important cellular roles. IPUT1 adds glucuronic acid residues to the lipids. When the glucuronic acid residues are not incorporated in the sphingolipids, the pollen is unable to mediate fertilization. Abstract: Glycosyl inositol phosphorylceramide (GIPC ) sphingolipids are a major class of lipids in fungi, protozoans, and plants. GIPCs are abundant in the plasma membrane in plants, comprising around a quarter of the total lipids in these membranes. Plant GIPCs contain unique glycan decorations that include a conserved glucuronic acid (GlcA) residue and various additional sugars; however, no proteins responsible for glycosylating GIPCs have been identified to date. Here, we show that the Arabidopsis thaliana protein INOSITOL PHOSPHORYLCERAMIDE GLUCURONOSYLTRANSFERASE1 (IPUT1) transfers GlcA from UDP-GlcA to GIPCs . To demonstrate IPUT1 activity, we introduced the IPUT1 gene together with genes for a UDP-glucose dehydrogenase from Arabidopsis and a human UDP-GlcA transporter into a yeast mutant deficient in the endogenous inositol phosphorylceramide (IPC ) mannosyltransferase. In this engineered yeast strain, IPUT1 transferred GlcA to IPC . Overexpression or silencing of IPUT1 in Nicotiana benthamiana resulted in an increase or a decrease, respectively, in IPC glucuronosyltransferase activity in vitro. Plants in which IPUT1 was silenced accumulated IPC, the immediate precursor, as well as ceramides and glucosylceramides. Plants overexpressing IPUT1 showed an increased content of GIPCs . Mutations in IPUT1 are not transmitted through pollen, indicating that these sphingolipids are essential in plants.